Strategi Pengembangan Energi Terbarukan: Keterlibatan Stakeholder dalam Meningkatkan Kesejahteraan Masyarakat - Rahadiyand Aditya; Sulistyary Ardiyantika; Abdul Aziz; Anisul Fuad (Politeknik Kesejahteraan Sosial Bandung, 2022)
The electrification rate in Indonesia has reached 98%, but most of it is still dominated by fossil energi and coal, whereas, in fact, the potential for renewable energi that is environmentally friendly has not been fully utilized. The micro hydro power plant in Andungbiru Village has been exploiting the natural potential since 1992 until now. Therefore, the researcher analyzes the renewable energi management strategy from the perspective of stakeholder involvement and the results it creates on the welfare of the community. This study uses a qualitative approach with data collection techniques using interviews, observation, and documentation. This study found that the concept of the quintuple helix is ​​found in the use of renewable energi. The role of the first helix is ​​the community as a driving force and initiator of the use of renewable energi. Furthermore, the role of the second helix is ​​for the private sector to encourage acceleration and acceleration in the process of utilizing renewable energi by providing financial assistance to maximize the potential for water flow and the development of the number of generating units. Furthermore, the role of the third helix is ​​academics who act as designers and experts in planning and technical development of the use of new and renewable energi. The fourth helix is ​​nature, where the natural potential in the form of a steady stream of water can be utilized properly. The fifth helix is ​​the government, the role of the government is to encourage the creation of legality for existing social-community groups, while also providing some training and improving the skills possessed by the community. Furthermore, the results of this study are that there are three major benefits from the derivative activities of utilizingthe natural potential for renewable energi, namely: 1) sufficient electricity needs of the community, 2) development of planting and livestock skills. 3) increasing knowledge of coffee cultivation and diversification